American Art at the 1897 Stockholm Exhibition. (1st October 2020) - Doe Stone, Elizabeth
Summary: On May 15, 1897, the Stockholm Exhibition of Arts and Industry opened in conjunction with the silver jubilee celebration of King Oscar II (r. 1872-1907). The Hall of Arts, designed by Ferdinand Boberg and organized by Prince Eugen, Sweden's "painting prince", not only celebrated the art of Scandinavia, but also advanced the country's cosmopolitan ambitions by exhibiting foreign art throughout the galleries. This article examines the overlooked presence of art from the United States at this exhibition, including the notable contributions of John Singer Sargent and James McNeill Whistler. By addressing the transnational critical reception of American art in Stockholm, this article considers the legacy of internationalism at the Stockholm Exhibition and its place within the broader history of late nineteenth-century Nordic-American exchange.